Religious change in market and consumer society: the current state of the field and new ways forward - Moberg, Marcus (Religion, 2018)
This article provides a critical appraisal of how the concept of the ‘market' has been understood and employed in previous scholarship on religion and religious change in market society. The discussion focuses on the respective virtues and weaknesses of approaches that view ‘religious markets' in terms of a de facto empirical entity on the one hand, and approaches that instead employ the ‘market' as a metaphor for how the religious field is structured and organized on the other hand. The article then proceeds to outline and argue for the adoption of a broader marketization-focused perspective that views ongoing changes in the religious field against the backdrop of wider neoliberal socio-economic restructurings of the global political economy and social institutional fields.